Unlocking the genetic variations in sesame (Sesamum indicum L.) germplasm for waterlogging tolerance: UNLOCKING THE GENETIC VARIATIONS IN SESAME GERMPLASM FOR WATERLOGGING TOLERANCE - NEMI CHAND JATAV; RAKESH CHOUDHARY; ARTIKA SINGH KUSHWAHA; S K CHATURVEDI (Journal of Oilseeds Research, 2021)
Undulating topographyand higher precipitation intensityleading towaterlogging during rainyseason adversely affects productivity of the kharif crops including sesame (Sesamum indicum L.) in Bundelkhand region. Limited information is available on existence of genetic variations for waterlogging tolerance in oilseed crops including sesame. In the present study, 609 germplasm accessions ofsesame were phenotyped under field conditions during kharif 2019 to identify accessions having waterlogging tolerance. Out of these 609 sesame accessions seven accessions viz., EC334449, EC334965, EC 334970, EC 334981, EC346727, IC204414 and IC96095 exhibited tolerance against waterlogging at three different growth stages (seedling stage, flower and capsule initiation stage) when natural waterlogging was allowed for 48 hours during experimentation. Identification of donors and development of waterlogging tolerant varieties is the most feasible and economically viable approach to bring desired stability in sesame production at the fields of resource poor farmers.